FISH analysis of brain smears obtained at intraoperative diagnosis – An accurate and fast method to detect 1p/19q-codeletion in gliomas. (October 2021) - Brown, Joanne; Byatt, Sally; Khan, Tayyaba; St Heaps, Luke; Dexter, Mark; Nahar, Najmun; Wong, Mark; Tan, King; Varikatt, Winny
Highlights: FISH for 1p/19-codeletion can be performed on fresh brain smears. Reliable and fast alternative to FISH on FFPE tissue. Helps to issue a prompt completed integrated diagnosis for optimal patient management. Abstract: The importance of molecular testing of gliomas is highlighted in the 2016 revised 4th edition of the WHO Classification of Tumours of the Central Nervous System, which applies an integrated diagnosis of histological and molecular features. In this classification system, oligodendrogliomas (ODG) are defined as IDH-mutant and 1p/19q-codeleted. Fluorescence in situ hybridization (FISH) analysis of formalin-fixed paraffin-embedded (FFPE) tissue is a standard method of determining 1p/19q-codeletion. However, it has several disadvantages, including requiring lengthy pretreatment, truncation artefact and lack of on-site access in many centers. In an effort to address these issues, we analysed FISH performed on smears obtained at intraoperative frozen section on 51 gliomas and compared this to FISH performed on subsequent FFPE sections. Four cases were excluded due to uninterpretable FISH results. Of the remaining 47 cases, 17 were concordant for 1p/19q-codeletion, 29 were concordant for lack of 1p/19q-codeletion, and 1 was discordant with 1p/19q-codeletion found on FFPE tissue but not on intraoperative smears. The discordant case was most likely due to sampling error, as the frozen section had not shown definite tumor. The FISH results on intraoperative smears were received within 24–48 h after the sample was collected, compared with 3–4 days for FFPE tissue. FISH on smears obtained at intraoperative frozen section is an accurate and fast method for determining 1p/19q-codeletion.